DRAC: a delta recurrent neural network-based arithmetic coding algorithm for edge computing - Shan, Bowei; Fang, Yong (Complex & intelligent systems, 2022)
This paper develops an arithmetic coding algorithm based on delta recurrent neural network for edge computing devices called DRAC. Our algorithm is implemented on a Xilinx Zynq 7000 Soc board. We evaluate DRAC with four datasets and compare it with the state-of-the-art compressor DeepZip. The experimental results show that DRAC outperforms DeepZip and achieves 5X speedup ratio and 20X power consumption saving.